Privacy paradox and privacy calculus: the dilemma and trade-offs of privacy protection among Chinese middle-aged and elderly under digital stress - Hao, Jingya; Pulido, Cristina M; Song, Yi (Frontiers in Psychology, 2025)
IntroductionDigitalization has reshaped everyday life while creating new privacy and security risks, which are particularly acute for middle-aged and older adults who entered the digital era relatively late. This study examines how Chinese middle-aged and elderly individuals perceive digital privacy risks and navigate the tension between privacy protection and everyday digital participation under digital stress.MethodsSix focus group discussions were conducted with 25 Chinese participants aged 45 and above, and the transcripts were analyzed using inductive qualitative content analysis.ResultsFindings reveal that while older adults show a high level of privacy awareness, their protective behaviors are shaped by culture, gaps in digital literacy, and structural dependence on digital infrastructures. Under digital stress, these constraints give rise to a privacy paradox in which individuals remain vigilant yet make strategic compromises to sustain digital participation.DiscussionThe findings suggest that the privacy paradox among Chinese middle-aged and elderly users is less an attitudinal inconsistency than a structural dilemma shaped by cultural norms, digital literacy gaps, and institutional dependence on digital infrastructures, highlighting the need for supportive designs and policies that reduce digital stress and strengthen privacy protection capabilities in later life.